Swift pocket reference : programming for iOS and OS X - Gray, Anthony (Computer programmer) (O'Reilly Media, 2015)
"Get quick answers for developing and debugging applications with Swift, Apple's multi-paradigm programming language. Updated to cover the latest features in Swift 2.1, this pocket reference is the perfect on-the-job tool for learning Swift's modern language features, including type safety, generics, type inference, closures, tuples, automatic memory management, and support for Unicode. Designed to work with Cocoa and Cocoa Touch, Swift can be used in tandem with Objective-C, and either language can call APIs implemented in the other. Swift is still evolving, but Apple clearly sees it as the future language of choice for iOS and OS X software development"--Back cover.